Mortality Salience in the News of Immigrant Perpetrators: Effects on Viewers' Emotion, Story Evaluation, and Perceived Crime Susceptibility. Issue 5 (20th October 2019) - Pan, Po-Lin; Zhou, Shuhua; Hayes, Marceline
Abstract: This study approaches the interplay between terror management and social identity theories to examine the individual and joint effects of mortality salience (MS) and social group difference (SGD). A 2 (MS: present/absent) × 2 (SGD: immigrant/nonimmigrant perpetrator) within-subjects repeated measures experiment was designed to study news viewers' negative emotion, story evaluation, and crime susceptibility. Results revealed that MS promoted higher negative emotion and better story evaluation but decreased crime susceptibility. TV news of immigrant perpetrators activated higher negative emotion and higher crime susceptibility, but not story evaluation. In addition, the joint effects of MS and SGD were significantly found on viewers' emotion, story evaluation, and crime susceptibility.